Christ Polymorphism in Jerusalem, Taphou 14: An Examination of Text and Image - McKay, Gretchen Kreahling (Apocrypha, 2003)
An episode of Christ's polymorphism involving Jesus' multiple manifestations to the Magi during the Adoration was recounted in an eighth-century sermon (with various attributions), and copied with illustrations in an eleventh-century manuscript: Jerusalem, Codex Taphou 14. The illustration of this specific polymorphous episode combined with the inclusion of the sermon itself, presents the modern audience with an intriguing glimpse into eleventh-century Byzantium. The sermon and image together raise issues related to the acceptance and availibility of apocryphal literature both in the eighth and eleventh centuries, and further adds to our understanding of the expansion of miniature cycles during the Middle Byzantine period.